Caracterização da liga Al-Fe-Cr-Ti obtida por compactação uniaxial a quente e comparação de sua microestrutura e propriedades com amostras produzidas por Fusão Seletiva a Laser - Teodoro, Nicole Silva (Universidade Federal de São Carlos, 2022)
Quasicrystalline phase former aluminum-based alloys have been drawing attention due to their characteristics of composite material, with a ductile matrix with quasicrystalline reinforcement of high hardness, showing mechanical strength at high temperatures. These composites are promissory mainly to the automobilist, aerospace industry and applications that require a thermal and electrical barrier, anti-corrosion and non-stick. Such characteristics are only possible due to the presence of quasicrystals phases (QC), which have an intermediate structure between the amorphous and crystalline. For the case of metastable QC-forming aluminum alloys, high cooling rates are needed so that QC phases can be formed. A process that allows the formation of metastable QC phases is gas atomization, however, this process turns to restrict the straight application since it produces a powder material. Therefore, it is necessary an additional process step to obtain a bulk geometry. In this context, the present work proposed to produce samples of the quasicrystalline phase former Al95Fe2Cr2T1 alloy, through Hot Uniaxial Pressure (HUP) of powder; a study doesn’t exist in the literature so far, with parameters of temperature (350, 400 and 450 °C) and pressure (1 and 1.5 GPa). Characterize its microstructure and mechanical properties and, finally, compare the reported results for the same alloy that was processed by Selective Laser Melting (SLM). The characterization of the produced samples by HUP included the quantification of voids, analyses of X-ray diffraction (DRX), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), microhardness Vickers, compressive mechanical tests, and fracture surfaces analysis. The minimum porosity of the samples was 0,3%. The DRX and DSC results have shown that QC phases suffer decomposition, mainly with the increase of the compaction process temperature. SEM reinforced the DRX and DSC results, showing the presence of spherical regular phases that decompose into irregular rosette-shaped phases, mainly when the temperature is increased. The optimized sample (450 °C and 1,5 GPa), obtained a compressive stress of 577 MPa, compressive strain of 30% and hardness of 130 HV. Through comparison of the results, the SLM process reported in the literature, demonstrated to be a more promising route to Al95Fe2Cr2Ti1 alloy, once it obtained samples with less porosity (0,05%), higher QC phase stability, which has shown to be significantly more refined, resulting in compressive strength of 792 ± 38 MPa at room temperature with 37 ± 8% of compressive strain and a microhardness of 180 HV.
Characterization of the Al-Fe-Cr-Ti alloy obtained by hot uniaxial pressure and comparison of its microstructure and properties with samples produced by Selective Laser Melting
Keywords: Quasicristais; Ligas de alumínio; Compactação uniaxial a quente; Fusão seletiva a laser; Quasicrystals; Aluminum alloys; Hot uniaxial pressure; Selective laser melting; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA